2021
DOI: 10.3390/agronomy11050896
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Target Shoot-Root Growth, Morpho-Physiological and Molecular Pathways to Induce Cadmium Tolerance in Vigna radiata L.

Abstract: Cadmium (Cd) inhibits plant growth, perturbs nutrient uptake, and affects chloroplast ultrastructure. The role of Cd stress in affecting growth and physiology and ameliorative effects of gibberellins (GAs) in Cd-induced toxicity in mung bean are lesser-known. This study comprehensively investigated Cd stress (CdCl2, IC50—500 µM L−1) with or without GA3 on mung bean (Vigna radiata L. Var. SML-668). In our methodology, a total of 80 mung bean plants (15 days old of uniform height) were divided into four groups, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…To stimulate plant growth and ward off the effects of stress, the common measures are the application of plant regulators [ 18 ]. In line with these findings, an increase in plant height in mung bean, lettuce, and rocket was conceivably the most widely observed effect of GA 3 [ 17 , 19 , 20 , 21 ]. GA 3 promotes plant development by promoting the degradation of DELLA proteins, a nuclear family of transcription factors that acts as repressors in GA 3 signaling pathways [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 54%
“…To stimulate plant growth and ward off the effects of stress, the common measures are the application of plant regulators [ 18 ]. In line with these findings, an increase in plant height in mung bean, lettuce, and rocket was conceivably the most widely observed effect of GA 3 [ 17 , 19 , 20 , 21 ]. GA 3 promotes plant development by promoting the degradation of DELLA proteins, a nuclear family of transcription factors that acts as repressors in GA 3 signaling pathways [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 54%
“…In great millet (Sorghum bicolor) seedlings, salinity stress (0, 100, and 200 mM NaCl) led to oxidative stress, reducing germination percentage, biomass, growth, and photosynthetic pigment content; exogenous GA 3 treatments (0, 144.3, 288.7, and 577.5 µM) and nitrogen fertilizer (0, 90, and 135 kg N ha −1 ) reduced the oxidative stress by increasing SOD and POD activities, thus improving photosynthesis and seedling growth (Ali et al, 2021). Hakla et al (2021) reported similar results in a study on mung bean (Vigna radiata) exposed to Cd toxicity (CdCl 2 , 500 µM); GA 3 at 500 µM improved the adverse effects of Cd stress on plant growth, photosynthetic apparatus, and metabolic processes. Salinity stress (150 mM NaCl) in wheat reduced germination, biomass, and photosynthetic pigments.…”
Section: Gibberellinsmentioning
confidence: 99%
“…This was suspected to be further increased due to the dramatic application of ash to agricultural soils and newly reclaimed ones. Using these agricultural soil types for cultivation will exacerbate the Cd stress encountered by plants; thus, the yield of crops decreases and the quality of field products gets degraded ( Abdel Latef, 2013 ; Hakla et al., 2021 ; Yaashikaa et al., 2022 ). Acute and chronic exposure to Cd can induce more damage including severe disturbance and downregulation in the physiological processes of plants, such as increased reactive oxygen and nitrogen species in the cells, which, in turn, act as deleterious molecules mediating an oxidative/nitrosative burst that could cause growth inhibition, accelerated senescence, and mostly cause plant death ( Noor et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%